UPGRADING STRATEGIES IN DISAGREEMENT AMONG INDONESIAN EFL LEARNERS - Nurul Choyimah (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
This study was aimed at finding out patterns of relationship between English language proficiency levels and upgrading strategies in disagreement by using conversation analysis. Students taking Seminar on Linguistics course in the School of Cultural Studies at Brawijaya University were selected as the subjects of this study. They were classified into pre-intermediate, intermediate, pre-advanced, and advanced levels. The analysis result show that students performed direct and indirect disagreement, each of which resulted in different upgrading strategies. Pre-intermediate, intermediate, and pre-advanced students dominantly used double negation strategy. Advanced level students never performed direct disagreement. Indirect disagreement used by students across proficiency were dominated by the use of you strategy